THE ROLE OF FATHER INVOLVEMENT IN BUILDING ADOLESCENT MENTAL HEALTH - Sari, Putri Puspita; Hanifah, Rulia; Dewi, Rini Liana; Riady, Muhammad Antos (EGALITA, 2025)
Abstract Fathers' involvement is often overlooked in the parenting discourse, despite its important role in shaping adolescents' mental health. However, related studies are scattered and have not been systematically reviewed. This review aims to examine fathers' involvement in parenting, the dimensions of involvement, its impact on adolescents' mental health, and factors that may moderate the relationship. This study is a Systematic literature review that follows the PRISMA 2020 guidelines. Articles were searched through PsycINFO, PubMed, Springer, Ebsco, Google Scholar, and Scopus databases using keywords such as "father involvement", "adolescent mental health", "parenting style", "father absence", "psychological well-being", "emotional regulation", "self-esteem", dan "behavioral problems. Of the 1,238 articles identified, 17 articles met the inclusion criteria and were analyzed further. Selection was done through identification, screening, and eligibility assessment. Data were analyzed using a thematic approach. Analysis of 17 studies showed that father involvement, including involvement including physical presence, emotional support, cognitive involvement, open communication, and role as a role model with various positive indicators in adolescents, such as increased self-esteem, decreased symptoms of depression and anxiety, and better emotional regulation skills. Factors such as child gender, family economic status, quality of father-mother relationship, and cultural background function as moderators in the relationship. Father involvement has a significant influence on shaping adolescent mental health and behavior. These findings highlight the importance of a more holistic and participatory parenting approach, as well as the need for family-based interventions that strengthen the role of fathers. Keywords: Father Involvement; Mental Health; Adolescents.Abstrak Keterlibatan ayah dalam pengasuhan masih sering diabaikan dalam pengasuhan anak, padahal memiliki peran penting dalam pembentukan kesehatan mental remaja. Namun, studi terkait masih tersebar dan belum dikaji secara sistematis. Tinjauan ini bertujuan untuk mengkaji keterlibatan ayah dalam pengasuhan, dimensi keterlibatan, dampaknya terhadap kesehatan mental remaja, serta faktor-faktor yang dapat memoderasi hubungan tersebut. Studi ini merupakan tinjauan pustaka sistematis yang mengikuti pedoman PRISMA 2020. Pencarian artikel dilakukan melalui database PsycINFO, PubMed, Springer, Ebsco, Google Scholar, dan Scopus menggunakan kata kunci seperti "father involvement", "adolescent mental health", "parenting style", "father absence", "psychological well-being", "emotional regulation", "self-esteem", dan "behavioral problems". Dari 1.238 artikel yang diidentifikasi, sebanyak 17 artikel memenuhi kriteria inklusi dan dianalisis lebih lanjut. Seleksi dilakukan melalui tahap identifikasi, penyaringan, dan penilaian kelayakan. Data dianalisis menggunakan pendekatan tematik. Analisis terhadap 17 studi menunjukkan keterlibatan ayah yang mencakup beberapa dimensi antara lain interaksi emosional dan afeksi, kehadiran fisik, pendidik, pelindung, dan dukungan finansial. Hal ini berkorelasi dengan berbagai indikator positif pada remaja, seperti peningkatan harga diri, penurunan gejala depresi dan kecemasan, serta kemampuan regulasi emosi yang lebih baik. Faktor-faktor yang memoderasi seperti jenis sosial budaya, ekonomi dan pekerjaan, faktor psikologis dan emosional, faktor relasi keluarga dan dukungan sosial. Keterlibatan ayah memiliki pengaruh signifikan dalam membentuk kesehatan mental dan perilaku remaja. Temuan ini menegaskan pentingnya pendekatan pengasuhan yang lebih holistik dan partisipatif, serta perlunya intervensi berbasis keluarga yang memperkuat peran ayah. Kata Kunci: Keterlibatan Ayah; Kesehatan Mental; Remaja.